Concept Application Analysis Green Tourism in the Development of Borobudur Temple as a Super Priority Destination - Susiyanto Susiyanto (Ideas Publishing, 2022)
Borobudur Temple is one of the super priority tourism destinations in Indonesia. Thus, it is necessary to develop efforts by the government, tourism object managers, and the local community to support the embedding of the designation by applying the concept of green tourism. This is what makes researchers interested in conducting literature studies related to the development of Borobudur Temple tourism objects based on the concept of green tourism. The results of this study found the fact that the development of tourist destinations at Borobudur Temple was supported by the improvement of access infrastructure to the location by the government, community empowerment through the Village Economic Center (Balkondes) which was initiated by the government but the manager was the local community, the use of electric vehicles around friendly tourist attractions environment, and digital promotion without damaging the environment by printing marketing materials.